GAMBARAN PENOLAKAN MASYARAKAT TERHADAP IMUNISASI DASAR LENGKAP BAGI BALITA (Studi di Kelurahan Sendangmulyo, Kecamatan Tembalang, Kota Semarang) - Pratiwi Sulistyani; Zahroh Shaluhiyah; Kusyogo Cahyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The coverage of basic immunization in Semarang City has met the target, yet there are still PD3I cases found such as 2 cases of diphtheria with 1 person died, 224 cases of measles and 8 cases of Acute Flaccid Paralysis (AFP). There are people in society who are reluctant to give immunizations because of the assumption that illegal immunization is still happening, despite statement from MUI Fatwa that immunization is permissible. The purpose of this study was to analyze the image of community refusals of complete basic immunization on children under five. The type of this research is qualitative research with ethnography study method. Data collection was done by in-depth interview and literature study, which the subjects were mothers who did not provide complete basic immunization in Sendangmulyo Village. The results showed that the reason why the subjects did not provide complete basic immunization to their children is due to misconception of immunization information they obtained. They got information from uncredible source that stated immunization is haram. The subjects were divided into 3 religious groups, namely Ahli Sunah Salafi, Nahdlatul Ulama (NU), and Jamaah Tabligh. These religious groups did not have a major effect on basic immunization practices by subject. Subjects’ belief in full basic immunization is influenced by the subjects and others’ experiences regarding immunization practices and myths. Research showed there was lack of support from parents, husbands, friends, cadres, and ustadz in basic immunization practices. Thus, information about the right immunization information that can be accessed easily by the public is urgently needed, as well as the need for health education on preventive effort of infectious diseases by Public Health Offices.